Honeybee products and edible insect powders improve locomotive and learning abilities of Ubiquilin-knockdown Drosophila - Patcharin Phokasem (2020)
BACKGROUND: Mutations in the human Ubiquilin 2 gene are associated with neurodegenerative diseases such as amyotrophic lateral sclerosis (ALS) with or without frontotemporal dementia (FTD), the fatal neurodegenerative disease that progressively affected neuronal cells in both brain and spinal cord. There is currently no effective therapy for these diseases. Over the last decade, researchers have focused on the potential use of natural products especially in neurodegenerative studies. Insect products have been used as traditional medicines, however, scientific information is still lacking. Fruit fly is recently used as a model organism to investigate degenerative diseases related to the nervous system because it has a short life span and produces a large number of offspring. METHODS: The present study investigated the effects of honeybee products and edible insect powders on the locomotive and learning abilities, neuromuscular junctions (NMJs) structure, and reactive oxygen species (ROS) in larval brains of Ubiquilin- knockdown Drosophila. RESULTS: dUbqn knockdown flies showed defects in locomotive and learning abilities accompanied with structural defects in NMJs. The results obtained revealed that the recovery of locomotive defects was significantly greater in dUbqn knockdown flies fed with coffee honey from Apis cerana (1% v/v) or Apis dorsata melittin (0.5 μg/ml) or wasp powder (2 mg/ml) than that of in untreated dUbqn knockdown flies. Furthermore, dUbqn knockdown flies fed with coffee honey showed the partial rescue of structural defects in NMJs, improved learning ability, and reduced the accumulation of ROS caused by dUbqn depletion in the brain over the untreated group. CONCLUSION: These results suggest that coffee honey from Apis cerana contains a neuroprotective agent that will contribute to the development of a novel treatment for ALS/FTD.